2009
DOI: 10.1016/j.jff.2009.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic properties of carotenoids: A potential role of maize as functional food

Abstract: XanthophyllsLutein Zeaxanthin Angiogenic inhibitor CAM assay A B S T R A C T Several human disorders are associated with neovascularization. The current in vivo study examines the effect in the blood vessel formation of a xanthophyll-rich seed extract of maize. The angiostatic effects of treatment with maize seed carotenoid extract (0.1-10 lM of zeaxanthin equivalent/implant) were evaluated in the chick yolk sac membrane (YSM) (12-50% inhibition, P < 0.05) as well as in the chorioallantoic membrane (CAM) assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 33 publications
(30 reference statements)
2
20
0
1
Order By: Relevance
“…Kurilich et al, [25] analyzed several different corn genotypes for the pigment content and found a level of lutein between 0.1 and 20µg/g while the level of zeaxanthin was between 0.01 and 8µg/g. Kuhnen et al, [26], analyzing a maize variety cultivated in southern Brazil, found a zeaxanthin content of 7µg/g and a lutein content of 3.7µg/g, a result comparable with the one obtained in this study. From HPLC analysis of the maize cultivars, a higher level of zeaxanthin than lutein was found in all the varieties examined except for the Haiti, where the level of the two carotenoids was almost the same.…”
Section: Discussionsupporting
confidence: 91%
“…Kurilich et al, [25] analyzed several different corn genotypes for the pigment content and found a level of lutein between 0.1 and 20µg/g while the level of zeaxanthin was between 0.01 and 8µg/g. Kuhnen et al, [26], analyzing a maize variety cultivated in southern Brazil, found a zeaxanthin content of 7µg/g and a lutein content of 3.7µg/g, a result comparable with the one obtained in this study. From HPLC analysis of the maize cultivars, a higher level of zeaxanthin than lutein was found in all the varieties examined except for the Haiti, where the level of the two carotenoids was almost the same.…”
Section: Discussionsupporting
confidence: 91%
“…Referring to grain yield, MPA1-C0 proved to be outstanding in two trials carried out in 2002/2003 and 2003/2004 in Canoinhas (SC), Brazil (26º10'37"; 50º23'43"). The results showed a variation in grain yield for 22 LMV (3.1 to 6.9 t ha ) make MPA1-C0 economically viable (Kuhnen et al, 2009;Kist et al, 2010;Kuhnen et al, 2010;, and due to this attribute it provides a potential way to improve the income of these farmers. When comparing the means of HSF obtained from the population evaluated in this study (MPA1-C1) with the value reported by Kuhnen et al (2011) in the original population (MPA1-C0), these authors observed an average that was slightly higher (18.8 µg g -1 ), although it is within the range of variation (11 to 23 µg g -1 ) found in this study.…”
Section: Resultsmentioning
confidence: 97%
“…The TCC was determined according to Lambert-Beer law, using a molar extinction coefficient (e) of 2,348 M -1 cm -1 (zeaxanthin), as described by Britton and Goodwin (1982). The molar extinction coefficient of zeaxanthin was used because this is the major carotenoid contained in the MPA1-C0 maize population (Kuhnen et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is increasing interest in these xanthophylls, since several benefits to human health have been attributed to them, e.g. antioxidant, protective activities against UV radiation, anti-angiogenic, reduction of the risk of atherosclerosis, anti-carcinogenic, and especially age-related macular degeneration (AMD) [2][3][4][5][6][7]. In fact, lutein is know to many as "the eye-protective nutriente" [8].…”
Section: Introductionmentioning
confidence: 99%